Single‐Chain Magnet Based on Cobalt(II) Thiocyanate as XXZ Spin Chain. Issue 13 (9th January 2020) - Rams, Michał; Jochim, Aleksej; Böhme, Michael; Lohmiller, Thomas; Ceglarska, Magdalena; Rams, Marek M.; Schnegg, Alexander; Plass, Winfried; Näther, Christian
Abstract: The cobalt(II) in [Co(NCS)2 (4‐methoxypyridine)2 ] n are linked by pairs of thiocyanate anions into linear chains. In contrast to a previous structure determination, two crystallographically independent cobalt(II) centers have been found to be present. In the antiferromagnetic state, below the critical temperature ( T c =3.94 K) and critical field ( H c =290 Oe), slow relaxations of the ferromagnetic chains are observed. They originate mainly from defects in the magnetic structure, which has been elucidated by micromagnetic Monte Carlo simulations and ac measurements using pristine and defect samples. The energy barriers of the relaxations are Δ τ 1 =44.9(5) K and Δ τ 2 =26.0(7) K for long and short spin chains, respectively. The spin excitation energy, measured by using frequency‐domain EPR spectroscopy, is 19.1 cm −1 and shifts 0.1 cm −1 due to the magnetic ordering. Ab initio calculations revealed easy‐axis anisotropy for both Co II centers, and also an exchange anisotropy Jxx / Jzz of 0.21. The XXZ anisotropic Heisenberg model (solved by using the density renormalization matrix group technique) was used to reconcile the specific heat, susceptibility, and EPR data. Abstract : Slowly relax… The magnetic properties of the linear chain compound [Co(NCS)2 (4‐methoxypyridine)2 ] n have been investigated both experimentally and theoretically. Slow relaxations of the ferromagnetic chains were observed in the antiferromagnetic state and the specific heat, susceptibility, and EPR data obtained have been reconciled by using the XXZ anisotropic Heisenberg model (see figure).